Effect of Land Use History on Biodiversity of Pine Plantations - Uribe, Sandra V.; García, Nicolás; Estades, Cristián F. (Frontiers in Ecology and Evolution, 2021)
The growing replacement of native vegetation by forest plantations is considered a global threat to biodiversity. Although plantation management can be designed to reduce its negative impacts, significant variation in biodiversity among stands with similar management suggests that previous land use might have an effect on the capacity of forest plantations to harbor native species. The goal of our study was to determine the effect of land-use history on the biodiversity currently present in pine plantations in the coastal range of Central Chile. In particular, we hypothesized that plantations that directly replaced native forests should have higher diversity of plants and birds than plantations that were established in agricultural areas. We also expected that plantations of higher number of rotations should have fewer habitat-specialists and more generalists/exotics, reflecting a process of biotic homogenization. Using aerial photographs and satellite images encompassing a period of six decades, we classified 108 4-ha sampling units into native forests, and mature (17-20y) pine plantations of first, second and third rotation, of either forest or agricultural origin. At each site, we collected data on the abundance and richness of diurnal birds and understory plants, and analyzed their behavior in relation to the land-use history using GLMs. Also, we evaluated dissimilarity of communities of each pine plantation “treatment” to assess the occurrence of biotic homogenization. As predicted, pine plantations that directly replaced native forests had a higher abundance of forest specialists and less abundance of exotics and generalists than plantations of agricultural origin. In contrast, the number of rotations of pine plantations not only did not affect negatively the diversity and abundance of forest specialist species, but the models showed some signs of naturalization in the studied systems over time, such as the increase in the abundance of native herbs and a reduction in the abundance of their exotic counterparts. These results agree with the lack of evidence for a decrease in the dissimilarity of biotic communties in plantations with time, suggesting that the management of pine plantations in Central Chile is not promoting biotic homogenization, beyond the impact of the initial stages of land use change.